Embedding Aligned Graphene Oxides in Polyelectrolytes to Facilitate Thermo‐Diffusion of Protons for High Ionic Thermoelectric Figure‐of‐Merit. (12th May 2021) - Jeong, Myunghwan; Noh, Juran; Islam, Md Zahidul; Kim, Kyomin; Sohn, Ahrum; Kim, Woochul; Yu, Choongho
Abstract: Recently emerged ionic thermoelectric conversion with the Soret effect is advantageous in providing large thermopower on the order of ≈ 1–10 mV K −1, but the origin of the large thermopower and the methodology of attaining superior thermoelectric performances are yet to be disclosed. Here, key parameters and their optimization for outstanding thermoelectric responses with polystyrene sulfonic acid (PSS‐H) are unveiled. It is found that the thermo‐diffusion of water boosts proton transport, playing a key role in obtaining large ionic thermopower by promoting unidirectional migration of protons from a hotter to colder side. When graphene oxide (GO) embedded in PSS‐H is aligned along the transport direction of protons and water, their diffusion along the in‐plane direction of GO is promoted, enlarging both ionic thermopower and ionic electrical conductivity. PSS‐H containing 3 wt% GO possesses extremely large ionic power factors up to 1.8 mW m −1 K −2 and ionic figure‐of‐merits up to 0.85 at 23 ° C. This study provides not only preeminent thermoelectric performances based on ion transport but also identifies the influence of the key parameters on thermoelectric properties, suggesting controllability of thermo‐diffusion of ions depending on inclusions in base materials, which will draw numerous subsequent research with their alterations. Abstract : The preferentially orientated graphene oxide in polystyrene sulfonic acid facilitated the thermo‐diffusion of water and thereby promoted proton transport under a temperature gradient, resulting in large ionic thermoelectric properties, thermopower, power factor, and figure‐of‐merit up to ≈13 mV K −1, ≈1.8 mW m −1 K −2, and ≈0.85 at 23 °C.